Religious harmony in Indonesia : need for new approaches - Yang, Jennifer Hui (2014)
Religious intolerance continues to bedevil Indonesia. Although the Indonesian constitution is committed to protecting religious freedom, there are certain laws and official actions that do not. Policymakers need to be proactive to build education, political and law enforcement capabilities to deal with religious intolerance.